Research Title: Sociology of Education in the Thought of Emile Durkheim - نوري, ناديا (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
There is no doubt that Emile Durkheim is rightfully considered a source and founder of the thought of the sociology of education in Europe and internationally. primarily a sociological phenomenon And renewing and highlighting its role in bringing about social balance in social institutions (family and school...) through ethics or what has become known today as the science of moral education, through which I worked to perpetuate the social character of education, unlike the individual visions that were prevalent in his time.